The effect of Powtoon learning media and inquiry learning models on students - Meydi Susanti; Suciati Suciati; Ajat Sudrajat (Inovasi Kurikulum, 2025)
The lack of technology utilization in the learning process and passive learning conditions result in students' involvement and learning outcomes being suboptimal. This study aims to analyze the effect of Powtoon learning media, utilizing inquiry learning methods, on affective learning outcomes and student involvement in learning. The type of research used is quasi-experimental. The subjects in this study were grade VI students from SDN 002 Barong Tongkok, comprising 30 students in the control class and 29 students in the experimental class. The data collection techniques employed included questionnaires, observations, and tests to assess the involvement and test results of students. The data analysis techniques used were descriptive and statistical tests. The results showed that the Powtoon media-assisted inquiry learning model had a significant effect on post-learning engagement. The inquiry learning model, assisted by Powtoon media, has a significant effect on cognitive and affective learning outcomes, as indicated by the results of the N-Gain calculation, categorized as moderate. It can be concluded that the Powtoon-assisted inquiry model learning can increase engagement and learning outcomes.   Abstrak Kurangnya pemanfaatan teknologi dalam proses pembelajaran dan kondisi pembelajaran yang pasif menyebabkan keterlibatan serta hasil belajar peserta didik kurang maksimal. Penelitian ini bertujuan untuk menganalisis pengaruh media pembelajaran Powtoon melalui metode pembelajaran inkuiri terhadap hasil belajar afektif dan keterlibatan peserta didik pada pembelajaran. Jenis penelitian yang digunakan adalah Kuasi Eksperimental. Subjek dalam penelitian ini adalah peserta didik kelas VI SDN 002 Barong Tongkok berjumlah 30 peserta didik untuk kelas kontrol dan 29 peserta didik kelas eksperimen. Teknik pengumpulan data yang digunakan adalah kuesioner, observasi, dan tes untuk mengetahui keterlibatan serta hasil tes peserta didik. Teknik analisis data yang digunakan yaitu uji deskripsi dan uji statistik. Hasil penelitian menunjukkan bahwa model pembelajaran inkuiri berbantuan media Powtoon berpengaruh signifikan terhadap keterlibatan pasca-pembelajaran. Model pembelajaran inkuiri berbantuan media Powtoon berpengaruh signifikan terhadap hasil belajar kognitif dan afektif dapat dilihat dari hasil perhitungan N-Gain dengan kategori sedang. Dapat disimpulkan bahwa pembelajaran model inkuiri berbantuan Powtoon dapat meningkatkan keterlibatan dan hasil belajar. Kata Kunci: hasil belajar; keterlibatan peserta didik; model inkuiri; Powtoon